Dairy effluent mitigates N2O missions while extreme precipitation stimulates N2O losses in a sandy soil - Yang, Cong; Liu, Deyan; Li, Ye; Li, Junjie; Zheng, Huijie; Dong, Yanhong; Yuan, Junji; Chen, Zengming; Chen, Lei; Ding, Weixin (Frontiers in Environmental Science, 2025)
Dairy effluents instead of mineral fertilizer can realize nutrients recycling while urease inhibitors have been proposed as fertilizer amendments to maximize nutrients utilization and reduce negative environmental effects. However, studies on the impacts of dairy effluent combined with urease inhibitors on nitrous oxide (N2O) and nitric oxide (NO) emissions remain limited. Here, a 2-year field trail with maize was conducted in a sandy soil with four treatments: no nitrogen (N) fertilizer (Control), mineral N fertilizer urea (NPK), fermented dairy effluent as liquid fertilizer (LF), and LF plus urease inhibitor hydroquinone (LFHQ). Cumulative N2O emission in the NPK treatment was 0.44 kg N ha‒1 during the 2021 maize season while drastically increased to 5.21 kg N ha‒1 during the 2022 maize season with extreme precipitation occurred, while NO emission reduced from 0.65 to 0.17 kg N ha‒1. Compared with the NPK treatment, N2O and NO emissions in the LF treatment decreased by 38.6% and 29.2%, and by 38.8% and 6.4% during the 2021 and 2022 maize seasons, respectively. Compared with the LF treatment, the LFHQ treatment increased N2O emissions by 40.7% and 21.7% during the 2021 and 2022 maize seasons, respectively. The N2O emission factors (EF-N2O) of applied N was 0.90–1.71% during the 2022 maize season, which was ten times greater than the 2021 maize season. We further evaluated correlation between EF-N2O of mineral N fertilizer and annual precipitation in temperate sandy soils by compiling published literature, suggesting that there was a quadratic relationship between EF-N2O and precipitation, with the highest EF-N2O occurring at ∼690 mm of precipitation. Accordingly, extreme precipitation would induce explosive N2O emissions at optimal scenario. Overall, our results suggest that replacing mineral fertilizers with dairy effluent mitigated N2O and NO emissions while heavy rainfall could cause N2O paroxysmal emission. Thus, rational water management in temperate farms is particularly required to avoid N2O surge emission after heavy rainfall events, and urease inhibitors co-application with nitrification inhibitors are recommended under dairy effluent application.